1998
DOI: 10.1080/036107398244175
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Entropy: Primary Versus Secondary Memory

Abstract: We report a spatial-memory scanning experiment that was used to measure age differences in entropy. A target grid consisting of four adjacent letters followed by the presentation of a single probe letter was presented on each trial. Half of the trials presented the probe stimulus in the same spatial position was the target letter (i.e., the probe letter was always a member of the positive set), and half of the trials transposed the target letter one, two, or three spaces of the right or left of the original ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…cardiovascular and metabolic factors [42], [43]. Apart from these facts, empirical evidence from other studies supports our observations of smaller variability in cognitive performance of older adults, which has been interpreted in the context of age-associated entropy or entropy states of the brain [44], [45].…”
Section: Discussionsupporting
confidence: 89%
“…cardiovascular and metabolic factors [42], [43]. Apart from these facts, empirical evidence from other studies supports our observations of smaller variability in cognitive performance of older adults, which has been interpreted in the context of age-associated entropy or entropy states of the brain [44], [45].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, age-comparative functional neuroimaging studies in humans have supported the prediction that neural distinctiveness decreases from early to late adulthood Carp et al, 2011;Goh et al, 2010;Park et al, 2004;Payer et al, 2006;Voss et al, 2008). At the same time, demonstrations of altered discriminal dispersion in humans have been sparse (but see Allen et al, 1998aAllen et al, , 1998bSara & Faubert, 2000). Informed by findings of increasing discriminal dispersion with greater STM load in younger adults (Anderson et al, 2011;Bays et al, 2009;Bays & Husain, 2008;Bays, Wu, & Husain, 2011;Fougnie et al, 2010;Zhang & Luck, 2008), we hypothesized that increasing set size would exacerbate age-related differences in discriminal dispersion, which we conceptualized as a behavioral indicator of the dispersion of probabilistic perceptual and memory representations.…”
Section: Rationale and Resultsmentioning
confidence: 99%
“…Our study was guided by the neural noise hypothesis of aging (Welford, 1981(Welford, , 1984 as well as related predictions of greater discriminal dispersion (Allen et al, 1998a(Allen et al, , 1998b, and reduced distinctiveness of neural representations (Li et al, 2000;Li & Sikström, 2002) with advancing adult age. Evidence from animal models (Hua et al, 2006;Liang et al, 2010;Yang et al, 2009) has suggested higher levels of neural noise in the aging nervous system.…”
Section: Rationale and Resultsmentioning
confidence: 99%
See 2 more Smart Citations